Structural Changes in a Li-Rich 0.5Li2MnO3*0.5LiMn0.4Ni0.4Co0.2O2 Cathode Material for Li-Ion Batteries: A Local Perspective. Issue 6 (25th February 2016) - Rana, Jatinkumar; Kloepsch, Richard; Li, Jie; Stan, Marian; Schumacher, Gerhard; Winter, Martin; Banhart, John
Abstract : Local structural changes in a Li-rich 0.5Li2 MnO3 * 0.5LiMn0.4 Ni0.4 Co0.2 O2 cathode material are investigated using X-ray absorption spectroscopy (XAS). The element-selective nature of XAS revealed the composite structure of the material, where both Li2 MnO3 and LiMn0.4 Ni0.4 Co0.2 O2 components exist as separate domains and also exhibit a distinct electrochemical response. An irreversible oxygen release from Li2 MnO3 domains contributes to a large irreversible capacity delivered by the material during activation and gives rise to the formation of a layered MnO2 -type structure. Lithium reinsertion into this layered MnO2 -type structure during discharge reforms the original Li2 MnO3 -type structure, which is lithium and oxygen deficient. The average valence state of Mn in Li2 MnO3 domains remains unchanged at 4+ during charge and discharge, suggesting an unusual participation of oxygen anions of Li2 MnO3 domains in redox processes. On the contrary, electrochemical processes in LiMn0.4 Ni0.4 Co0.2 O2 domains involve conventional redox processes of transition-metal (TM) ions. In addition to Ni 2+ /Ni 4+ and Co 3+ /Co 4+ redox reactions, a small amount of Mn 3+ detected in LiMn0.4 Ni0.4 Co0.2 O2 domains also participates in electrochemical processes via a Mn 3+ /Mn 4+ redox reaction. All structural modifications introduced into the material during activation are recovered upon discharge to 2.5 V, except those caused by the permanent removal of oxygen from Li2 MnO3 domains.